Barnet i haven - en analyse af et grundtvigsk motiv og dets rødder i en tidlig litterær tradition - Wigh-Poulsen, Henrik (Grundtvig-studier, 1996)
The Child in the Garden By Henrik Wigh-Poulsen In the poems, .Udby Have. (The Garden of Udby) and .Til Sibbern. (To Sibbern) - from the collection » Nytaarsgave« (New Years Gift), 1812 - Grundtvig describes his homecoming in the summer of 1811 after his dramatic crisis of faith the same winter. He describes his homecoming to the idyllic countryside, to his father’s house, to the garden of his childhood, and, first and foremost, to Christianity.In the poem .Til Sibbern., Grundtvig - at that time a curate in his father’s parish - addresses his friend, Sibbern. Writing in his parents’ garden on a fine summer’s day, Grundtvig looks back upon his recent flight from Copenhagen, his ordination, and the comfort and courage he gathered while reading his New Testament, resting on a stone on the edge of some small forest, just before his arrival at the place where he grew up.This place, the home and the garden of his childhood, is the main subject of the other poem, .Udby Have.. The garden, encircling the old rectory, has witnessed his childhood and his childish absorption in the historical books from his father’s library.In the garden he became devoted to » Saga«, and with the faith of the child he learned the true humble and innocent attitude towards her. The garden has also witnessed his years of growth, his departures and homecomings, his doubts, his crisis of faith, and his final conversion, and now his permanent peace of mind. At the time of writing this poem, Grundtvig has regained the true attitude of childish innocence. He has refound God and » Saga«.The article argues that several of the themes found in the two poems - themes of coming home to the garden and countryside, of growing up, of losing and regaining the paradise of childhood, of preparing for greater tasks - all originate in a broader literary tradition, the .pastoral.. The pastoral has its roots in both Biblical and secular writing and was an influential genre in the 18th century as well as in the period of Romanticism, although in different forms.Furthermore, it is argued that Grundtvig uses this pastoral tradition in two different ways. First, in direct opposition, scorning the shallow, ornamental poetry of nature of the 18th century. Second, as it has been shown, he uses the pastoral tradition as a creative element with strong romantic implications and Biblical associations, to depict the regained innocence and belief of the child.